DOI: 10.14264/uql.2015.839
|View full text |Cite
|
Sign up to set email alerts
|

A cyclone-proof community centre for Atherton: tropical monumentality to enable resilience in Far North Queensland communities

Abstract: This research thesis aims to mobilise Queensland Government funding destined to the construction of public cyclone shelters to address the higher goal of enhancing community resilience of inland Far North Queensland (FNQ) communities threatened by cyclonic events.The thesis comprises a written portion and a design proposal for a cyclone-proof community centre in Atherton, ninety kilometres south-west of Cairns, the main city of FNQ. The applied strategy seeks to surpass the limited and mono-functional governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The good-practice examples were analysed according to four criteria as identified by Bischeri (2015): location, function, compositional strategies and formal expression, and community involvement. For the location and function criteria, the determination of the significance of a facility’s location or function in terms of its strategic or symbolic roles for the targeted community has been taken into account as previous studies have shown that memories and community identity were very often the only possessions left to the survivors (Bischeri, 2015).…”
Section: Project Reviewmentioning
confidence: 99%
“…The good-practice examples were analysed according to four criteria as identified by Bischeri (2015): location, function, compositional strategies and formal expression, and community involvement. For the location and function criteria, the determination of the significance of a facility’s location or function in terms of its strategic or symbolic roles for the targeted community has been taken into account as previous studies have shown that memories and community identity were very often the only possessions left to the survivors (Bischeri, 2015).…”
Section: Project Reviewmentioning
confidence: 99%